Синяя Борода и другие сказки - Яхнин Леонид Львович (Золотая радуга, 2017)
Экземпляры: Ф-22 (20191119) / Инвентарный номер: 94697 / Цена: / Сис.шифр: 84(0)-4 / Авт.знак: С 38 / ГРНТИ: 17.82.93 / ББК: 84(0)-4